Geometrical design of 3D superconducting diodes - Philip JW Moll (Communications Materials)
Abstract The design of advanced functionality in superconducting electronics usually focuses on materials engineering, either in heterostructures or in compounds of unconventional quantum materials. Here we demonstrate a different strategy to bespoke function by controlling the 3D shape of superconductors on the micron-scale. As a demonstration, a large superconducting diode effect is engineered solely by 3D shape design of a conventional superconductor, ion-beam deposited tungsten. Its highly efficient diode behavior appears from its triangular cross-section when vortices break time-reversal and all mirror symmetries. Interestingly reciprocity is observed at four low-symmetry field angles where diode behavior would be expected. This can be understood as a geometric mechanism unique to triangular superconductors. Geometry and topology induce a rich internal structure due to the high-dimensional tuning parameter space of 3D microstructures, inaccessible to the conventional 2D design strategies in thin films.